Loss of aldehyde dehydrogenase in an Escherichia coli mutant selected for growth on the rare sugar L-galactose. - Zhu, Y (1987)
Escherichia coli K-12 converts L-fucose to dihydroxyacetone phosphate (C-1 to C-3) and L-lactaldehyde (C-4 to C-6) by a pathway specified by the fuc regulon. Aerobically, L-lactaldehyde serves as a carbon and energy source by the action of an aldehyde dehydrogenase of broad specificity; the product, L-lactate, is then converted to pyruvate. Anaerobically, L-lactaldehyde serves as an electron acceptor to regenerate NAD from NADH by the action of an oxidoreductase; the reduced product, L-12-propanediol, is excreted. A strain selected for growth on L-galactose (a structural analog of L-fucose) acquired a broadened inducer specificity because of an altered fucR gene encoding the activator protein for the fuc regulon (Y. Zhu and E. C. C. Lin, J. Mol. Evol. 23:259-266, 1986). In this study, a second mutation that abolished aldehyde dehydrogenase activity was discovered. The L-fucose pathway converts L-galactose to dihydroxyacetone phosphate and L-glyceraldehyde. Aldehyde dehydrogenase then converts L-glyceraldehyde to L-glycerate, which is toxic. Loss of the dehydrogenase averts the toxicity during growth on L-galactose, but reduces by one-half the aerobic growth yield on L-fucose. When mutant cells induced in the L-fucose system were incubated with radioactive L-fucose, accumulation of radioactivity occurred if the substrate was labeled at C-1 but not if it was labeled C-6. Complete aerobic utilization of carbons 4 through 6 of L-fucose depends not only on an adequate activity of aldehyde dehydrogenase to trap L-lactaldehyde as its anionic acid but also on the lack of L-1,2-propanediol oxidoreductase activity, which converts L-lactaldehyde to a readily excreted alcohol.